2007
DOI: 10.1001/jama.298.23.2754
|View full text |Cite
|
Sign up to set email alerts
|

“False-Positive” Cardiac Catheterization Laboratory Activation Among Patients With Suspected ST-Segment Elevation Myocardial Infarction

Abstract: ESPITE ITS LIMITATIONS, THEstandard 12-lead electrocardiogram (ECG) remains a key diagnostic tool directing the emergency management of patients with an acute myocardial infarction. 1 In 1980, DeWood et al 2 reported that patients presenting with acute chest pain, persistent ST-segment elevation progressing to Q waves, and elevations of cardiac biomarker levels were found to have a total thrombotic coronary occlusion in 87% of cases. A variety of other serious conditions aside from an acute myocardial infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
3
13

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(194 citation statements)
references
References 29 publications
12
164
3
13
Order By: Relevance
“…If we consider only those patients actually treated by primary PCI or emergency coronary bypass surgery as true positive referrals, the number of false positives still amounts to only 5.9%. This is considerably lower than reported recently by American colleagues (14%), 5 and can be regarded as an important indication of the quality of the triage system in our country. These better results may be due to a wellorganised chain of care for primary PCI including prehospital (computer-assisted) ECG interpretation as well as a customised communication system between ambulance services and primary PCI centre.…”
contrasting
confidence: 61%
“…If we consider only those patients actually treated by primary PCI or emergency coronary bypass surgery as true positive referrals, the number of false positives still amounts to only 5.9%. This is considerably lower than reported recently by American colleagues (14%), 5 and can be regarded as an important indication of the quality of the triage system in our country. These better results may be due to a wellorganised chain of care for primary PCI including prehospital (computer-assisted) ECG interpretation as well as a customised communication system between ambulance services and primary PCI centre.…”
contrasting
confidence: 61%
“…A study from 2007 showed an approximate 10 % rate of normal coronaries in patients who are referred for immediate PCI for STEMI; in this study, false positives were underestimated because patients with non-STEMI, and sometimes those with simple stable coronary disease, were not considered false positives [14]. In a study by Kontos et al [13], false positives were assessed by use of millimeter criteria, which may be very nonspecific [15].…”
Section: Pseudoinfarction Missed Stemi and Appropriate Cath Lab Actmentioning
confidence: 84%
“…Thus, studies looking at false positive rates use as outcome measures: (1) an ''expert'' interpretation [16] or; (2) the presence of a positive biomarker (troponin) at any level and an angiographic culprit lesion, whether occluded or not [14] or; (3) STE criteria [13]. In a different study by Kontos et al [21], of LBBB, there was an assessment of biomarker level (CK-MB) at 5 9 the upper limit of normal.…”
Section: Pseudoinfarction Missed Stemi and Appropriate Cath Lab Actmentioning
confidence: 99%
“…Es importante destacar que 7-10% de los pacientes con diagnóstico inicial de SCA no presentan lesiones coronarias signifi cativas y en muchas ocasiones es difícil establecer un diagnóstico preciso 10,11 . También es esencial el diagnóstico diferencial con IAM y miocarditis, por su implicancia pronóstica y terapéutica.…”
Section: Discussionunclassified